2018
DOI: 10.1109/tii.2018.2810323
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Assessment of COTS Converters-Based DC Integrated Power Systems in Electric Ships

Abstract: Maritime applications have found in the integration of the electric power system a way to further improve efficiency and reduce the weight of new electric ships. This movement has led scientists to integrate smart management systems to optimize the overall behavior of the grid. In this context, power electronics play a key role in linking the different elements of the power architecture. Moreover, the transition towards a dc distribution, which has already been established in other applications, is being regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Furthermore, nonlinear structures like the Wiener-Hammerstein approach [14] or the polytopic approach [17] have been also proposed for DC-DC converters. More recently, some new strategies have been proposed: to consider the effect of system-level controllers [19,20,27,28], to improve the performance of the model in case strong nonlinearities are present in the system [29], or the first approach towards a blackbox large-signal stability analysis [30]. A review about blackbox modeling structures for DC-DC converters can be found in [31].…”
Section: Blackbox Modelingmentioning
confidence: 99%
“…Furthermore, nonlinear structures like the Wiener-Hammerstein approach [14] or the polytopic approach [17] have been also proposed for DC-DC converters. More recently, some new strategies have been proposed: to consider the effect of system-level controllers [19,20,27,28], to improve the performance of the model in case strong nonlinearities are present in the system [29], or the first approach towards a blackbox large-signal stability analysis [30]. A review about blackbox modeling structures for DC-DC converters can be found in [31].…”
Section: Blackbox Modelingmentioning
confidence: 99%
“…This filter could also be a weighted combination of local filter, as the characteristic polynomial can depend on the operating point. This methodology has been applied to EPCs with nonlinear dynamic behavior when the inputs change sharply showing a high accuracy [9], [18]. However, in case the dynamic behavior of the different small-signal models is substantially different, the accuracy of this approach can also be compromised.…”
Section: Dynamic Weighting Functionsmentioning
confidence: 99%
“…The polytopic model is able to reproduce the nonlinear dynamic behavior of EPCs when small perturbations are applied in different operating points, when large-signal and slow perturbations are introduced, or when the nonlinearities of the converter are soft. For instance, these structures have been applied to model dc microgrids integrating different converters using system-level control strategies [7]- [9]. However, when the dynamic nonlinearities are strong and the variations of the input variables are sharp, the accuracy of the model is compromised.…”
Section: Introductionmentioning
confidence: 99%
“…The generation side scheduling problem is formulated as a deterministic optimization problem where the objective is defined as minimizing the fuel consumption cost of the system over the study period: (16) • Energy Storage System: The amount of available energy in the ESS can be estimated based on (6). However, the upper and the lower boundary for charging and discharging power of the system as well the system capacity are considered as in 17 (19) Note that pch/dch(t) is determine by control parameter of u(t) in (17), where u(t)=1 denotes discharging, and u(t) =0 shows charging process.…”
Section: A Objective Functionmentioning
confidence: 99%
“…By the use of ESS aboard, DGs can be dispatched in a way to share the load proportionally while being operated at (or near) maximum-efficiency point. It this perspective, ESSs act as back-up units that not-only energize the platform during the peak-load periods with lower costs and improve the dynamic behavior of the system, but also help reduction of pollutant emissions through avoiding unnecessary conventional unit commitments [6]. The energy management of on-board hybrid power system with energy storage are discussed in [7]- [11].…”
Section: Introductionmentioning
confidence: 99%